O laudo médico-legal como fonte de informação e seu papel social - ARRUDA, Maria Izabel Moreira (Instituto Brasileiro de Informação em Ciência e Tecnologia/Universidade Federal do Rio de Janeiro, 2017)
The study of the legal-medical report as information source, in its aspects of archive documents and informational contents, identifying scenery and the social characters involved in the creation, preservation, transferance, dissemination and use of information, in particular the Legal Medicine and the experts. Its typology is built, as well as attributes, functions, aplications and main constituent parts, besides the concepts and definitions of legal medicine, the specific literature and its most important authors, publications, services and information products, including the Internet. Using this analysis, it s possible to define the data base site for automation, and therefore, hasten the recovering and utilization process of these informations. The medical report, approached in the sphere of action of the police and the justice is emphasized in its social importance, considering the nowadays violence and criminality that characterizes our world at the present time.